2013
DOI: 10.1073/pnas.1300981110
|View full text |Cite
|
Sign up to set email alerts
|

Shigella impairs T lymphocyte dynamics in vivo

Abstract: The Gram-negative enteroinvasive bacterium Shigella flexneri is responsible for the endemic form of bacillary dysentery, an acute rectocolitis in humans. S. flexneri uses a type III secretion system to inject effector proteins into host cells, thus diverting cellular functions to its own benefit. Protective immunity to reinfection requires several rounds of infection to be elicited and is short-lasting, suggesting that S. flexneri interferes with the priming of specific immunity. Considering the key role playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 42 publications
4
43
0
Order By: Relevance
“…Cells transfected with IpgD-GFP and incubated with CXCL12 had no ERM protein localization at the pole, preventing T-cell polarization and migration (Konradt et al, 2011). Mean velocity of T-cells was measured in vivo , with uninfected T-cells exhibiting 9 and 4 μm/min for wild-type Shigella -infected T-cells (Salgado-Pabón et al, 2013). This indicates that Shigella is capable of affecting T-cells in the context of infection, and that this ability is dependent on IpgD.…”
Section: Discussionmentioning
confidence: 99%
“…Cells transfected with IpgD-GFP and incubated with CXCL12 had no ERM protein localization at the pole, preventing T-cell polarization and migration (Konradt et al, 2011). Mean velocity of T-cells was measured in vivo , with uninfected T-cells exhibiting 9 and 4 μm/min for wild-type Shigella -infected T-cells (Salgado-Pabón et al, 2013). This indicates that Shigella is capable of affecting T-cells in the context of infection, and that this ability is dependent on IpgD.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasome-induced cellular stiffening and arrest may represent a general mechanism for the control of intracellular bacterial infection. Earlier work showed that CD4 + T lymphocytes infected with Shigella flexneri exhibit an impaired ability to migrate in vitro and in vivo (34,35). Shigella can drive inflammasome activation through both NLRC4 and NLRP3 (36,37), but it remains to be determined whether increased cell stiffness and impaired movement in immune cells are a consequence of inflammasome activity induced by pathogens other than Salmonella, such as Shigella or Listeria.…”
Section: Discussionmentioning
confidence: 99%
“…To understand why several rounds of Shigella infection induce only a short-term protective humoral immunity and thus overcome the challenges of vaccine development (3,4), a better knowledge of Shigella-immune cell interactions is necessary. Over the last years, Shigella has been shown to not only target innate immune cells (5) but also to directly impact adaptive immune cells through mechanisms dependent upon its T3SS (6)(7)(8). Our previous studies of Shigella-lymphocytes cross talks suggested that, besides invasion of these cells, injection of Shigella T3SS effectors not resulting in invasion might also occur (6).…”
mentioning
confidence: 99%